Minero-petrographic characterization of white marble Roman finds from P.A. Garda Museum (Ivrea, TO). Issue 1 (1st April 2022) - Storta, E; Borghi, A; Mantovani, P; Deodato, A; Perotti, L; Sani, A
Abstract: The work provides a minero-petrographic characterization of the main roman finds in white marble of the Garda Civic Museum of Ivrea (Piemonte, Northern Italy). A multi-analytical approach based on optical and scanning electron microscopy, electron microprobe and stable isotope analyses has been performed. The chemical composition of the main mineral component (calcite and/or dolomite), and of subordinate or accessory minerals useful for discriminative purposes were attained. A database for archaeometric purposes of the artefacts was achieved and a comparison with the Italian and Mediterranean marbles reported in the literature was implemented. The marbles resulted generally of Alpine provenance. This suggests that Eporedia (the old name of Ivrea) in Roman times was a site of local importance, with the employment of goods coming from trade routes connected with the surrounding alpine areas.